2010
DOI: 10.1007/s11916-010-0097-7
|View full text |Cite
|
Sign up to set email alerts
|

Allodynia in Cluster Headache

Abstract: Cutaneous allodynia (CA), the perception of pain when a non-noxious stimulus is applied to normal skin, has been described in various pain syndromes. The pathophysiology of CA in headache is thought to be related to central sensitization of brainstem, and possibly thalamic, neurons. The recognition of CA in cluster headache (CH) is recent, and available data are scant. Some studies suggest the occurrence of CA in a significant proportion of CH patients. However, one study that examined sensory thresholds in CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Current theories attribute to central sensitization an important role in tension type headache pathogenesis [ 36 - 38 ] with evidence of allodynia symptoms in chronic forms [ 38 ], as confirmed by present results. In regard to cluster headache, previous studies reported allodynia during cluster episodes, in accord with present results [ 39 ], while this is the first study suggesting the presence of allodynia in other TACs, as paroxysmal migraine and hemicranias continua. Actually we cannot advance conclusions on reduced expression of allodynia in the mixed headaches group, which was a very heterogeneous group and worthy of further case series enlargement, considering the importance of a better knowledge of these rare disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Current theories attribute to central sensitization an important role in tension type headache pathogenesis [ 36 - 38 ] with evidence of allodynia symptoms in chronic forms [ 38 ], as confirmed by present results. In regard to cluster headache, previous studies reported allodynia during cluster episodes, in accord with present results [ 39 ], while this is the first study suggesting the presence of allodynia in other TACs, as paroxysmal migraine and hemicranias continua. Actually we cannot advance conclusions on reduced expression of allodynia in the mixed headaches group, which was a very heterogeneous group and worthy of further case series enlargement, considering the importance of a better knowledge of these rare disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Given the presence of allodynia in other primary headache disorders, these data may also have implications for conditions such as cluster and tension-type headache [2; 8]. Our findings show that the primed state can develop following a single exposure of the dura to IL-6 or a single injection of i.c.…”
Section: Discussionmentioning
confidence: 62%
“…Both the extent to which the mechanisms of allodynia are shared across different headache syndromes and the identity of the specific aspects that may be syndrome-specific remain unknown. However, a previous study has suggested that the presence of allodynia not only contributes to our understanding of the pathophysiological mechanism of CH but may also be helpful in determining the treatment and predicting the therapeutic response ( 40 ). In our study, there was no significant difference in the presence of or scores for cutaneous allodynia between those with probable CH and those with definite CH.…”
Section: Discussionmentioning
confidence: 99%